Pemetaan Capaian Pembelajaran dan Materi Ajar PAI dan Budi Pekerti Elemen Fiqih dalam Kurikulum Merdeka - Mushthofa, Fadhlan Ghufron; Fakhruddin, Agus; Romli, Usup (The Magister of Islamic Education IAIN Pontianak, 2025)
Differences in views between fiqh madhhabs often trigger debates, both in society and academia. Not infrequently, these differences lead to serious conflicts. This study aims to map the learning outcomes and teaching materials for Islamic Religious Education (PAI) and Budi Pekerti, especially the Fiqh element in the Merdeka Curriculum, based on the opinions of the madhhabs. This research seeks to identify which madzhab is most dominantly used in teaching materials, as well as provide convenience for educators in designing learning methods that are in accordance with the characteristics of students and the applicable curriculum. The research method used is a qualitative approach with content analysis techniques. The results show that PAI teaching materials in the Merdeka Curriculum are mapped by referring to the opinions of one particular madhhab, although in some parts other madhhab views are found. This finding is expected to be a reference for educators in developing inclusive and contextual learning strategies.